Oricymba rhynchocephala sp. nov., a new cymbelloid diatom (Bacillariophyceae) from Xianju National Park in Zhejiang Province, China - Zhang, Wei; Shang, Guang-Xia; Kociolek, J. Patrick; Wang, Li-Qing; Zhang, Rui-Lei (Phytotaxa, 2018)
During a survey of freshwater diatoms from Xuedong stream in the Xianju National Park, Zhejiang Province, China, a new cymbelloid species, Oricymba rhynchocephala sp. nov. has been recorded. This species is assigned to the genus Oricymba by virtue of having a ridge separating the valve face and mantle, the presence of apical pore fields, stigma with a single external opening but two internal openings, and areolae with dentate occlusions. A detailed morphological description of the new species, O. rhynchocephala, is presented, based on light and scanning electron microscopy. Oricymba rhynchocephala sp. nov. is characterized by having a linear-lanceolate outline with slightly arched valve margins towards rounded and clearly rostrate apices, as well as radiate striae. The taxon is morphologically compared with similar species of the genus Oricymba. The new species, can be easily separated from other species in Oricymba by its obvious rostrate apices. The report of this new species from Zhejiang Province adds to our understanding the morphology and distribution of the genus Oricymba in China.